E pluribus plures: Shock dependency of the USD pass-through to real and financial variables - Massimo Minesso Ferrari; Johannes Gräb (European Central Bank (ECB), 2022)
This paper quantifies the pass-through of a US dollar appreciation on trade variables and domestic financial conditions in a panel of 34 countries. Pass-through coefficients are highly shock-dependent: if the appreciation is driven by a US expansionary shock, the positive effects of stronger global demand - the "real" channel-dominate the negative effects of a stronger dollar - the "exchange rate" channel. As a result, a positive US demand (supply)-drive appreciation expands global trade and stock valuations up to 2.2 (2.5) and 8% (15%) respectively, while if the appreciation is driven by a monetary policy shock the sign is opposite, leading to a contraction in the order of 2.5% (3%) depending on the country. The coefficients also exhibit a large degree of cross-country heterogeneity, we find that financial and trade exposure to the US, trade openness and USD invoicing shares explain up to 60% of the USD pass-through after demand and supply shocks. Crosscountry differences, instead, are not explained by dollar invoicing if monetary policy or risk shocks determine USD movements. We explain this finding with the endogenous policy reaction of monetary authorities in emerging markets that stabilizes the exchange rate against the dollar and weakens the invoicing channel of dollar shocks.
Keywords: F31; F41; F44; E44; E32; 330; Exchange rate; USD; pass-through; VAR